Reintroducing public actors in entrepreneurial dynamics: A co‐evolutionary approach to categorization. (19th August 2019) - Demil, Benoît
Abstract: Research Summary: Categories are important cognitive and social interfaces for entrepreneurs and new ventures. However, the categories forged by the state and public agencies have been largely overlooked by the literature. A historical narrative explores the categorization process to register French mail order companies in an administrative nomenclature. This categorization performs reality by providing legality to a new population and by producing enduring social boundaries. Moreover, the historical reasoning enables to assimilate the emergence of a new category with a co‐evolutionary process, avoiding the reification of categories by considering multilevel interactions. Finally, our narrative highlights the need to consider the interests of entrepreneurs and public actors symmetrically. Managerial Summary: How do the state and public agencies categorize new activities? Such categorization can have substantial consequences for entrepreneurs in terms of subsidies, regulation, or control. A historical narrative is built to trace the emergence of the French mail order category in a public nomenclature. This narrative suggests that the categorization results from the convergence of three evolutions over time: a growing interest of public policy in retailing; the development of the French statistical apparatus after world war II (WWII); and the collective entrepreneurship of the mail order companies. Entrepreneurs should consequently dedicate attention to the tools for recording economic activity, be aware of windows of opportunity occurring in the categorization process and eventually take action to influence the way they are categorized.